THE INFLUENCE OF TIKTOK SALES PROMOTION (DISCOUNT VOUCHERS) AND CUSTOMER SATISFACTION ON REPURCHASE INTENTION OF AYAM BERSIH BERKAH CONSUMERS IN CIPARAY DISTRICT - Siti Mulyani; Agung Pramudya (PT. Jurnal Center Indonesia Publisher, 2026)
This study is motivated by the increasing use of TikTok as a digital promotional medium through discount vouchers. In an increasingly competitive business environment, digital promotion not only aims to attract consumer interest but also to enhance customer satisfaction in order to encourage repeat purchases. Ayam Bersih Berkah in Ciparay District utilizes TikTok sales promotions as a digital marketing strategy to retain its customers. The purpose of this study is to examine the effect of TikTok sales promotions (discount vouchers) and customer satisfaction on consumers’ repurchase intention at Ayam Bersih Berkah in Ciparay District. This research employs a quantitative method with descriptive and verificative approaches. Data were collected through questionnaires distributed to consumers who had purchased Ayam Bersih Berkah products via TikTok. The research population consisted of consumers over a one-year period, and the sample was determined using the Slovin formula, resulting in 100 respondents. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, and F-tests with SPSS version 25. The results indicate that TikTok sales promotions (discount vouchers) and customer satisfaction have a positive and significant effect on repurchase intention, both partially and simultaneously. Therefore, it can be concluded that effective TikTok sales promotions supported by high customer satisfaction can encourage sustainable repeat purchases.